Analysis of the Explosion of the Pertamina Plumpang Depo in Review From Government Regulation No. 14 of 2015 Concerning the National Development Master Plan - Khaerunisa, Kamila; Ratnadewanti, Dewi; Alvandi, Agung; Hotimah, Husnul; Antoni, Herli (Universitas PGRI Madiun, 2023)
At present, industrial progress has been very rapid in various parts of the world, not to be missed in Indonesia. One of the industries engaged in Indonesia is oil and gas which is held by PT. Pertamina. The Pertamina Plumpang depot, where the oil is stored, has experienced two fires, first in January 2009 and also in March 2023 which spread to residents' settlements. The problem that was revealed after the plummpang incident was that the government could judge that the issuance of a building permit (IMB) was not the right decision, moreover the settlement is very close to the Pertamina depot which is at risk of fire hazard. This paper aims to provide an understanding of how this can happen and who will be responsible in this casebased on Government Regulation number 14 of 2015 concerning the National Development Master Plan. This paper was prepared based on a descriptive qualitative research method, with a case study approach. It can be concluded that the second explosion of the Plummpang depot which caused many victims of residents was due to the finding of an inaccurate IMB grant